A LEGAL REVIEW OF FOOD POLICY IN ACHIEVING RICE SELF SUFFICIENCY IN SOUTH LABUHANBATU REGENCY, INDONESIA - Rahmat Suhargon; Syafrial Syah; Ulfa Aulia Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The title of this research is “A Legal Review of Food Policy in Achieving Rice Self-Sufficiency in South Labuhanbatu Regency, Indonesia”. This research’s object is the Indonesian legal policy on food. The objective is to analyze food policy from a legal perspective, assess its implementation at the regional level, and formulate adaptive and applicable legal recommendations to support sustainable food self-sufficiency in South Labuhanbatu Regency. This research is also expected to identify legal loopholes and implementation barriers that hinder the achievement of self-sufficiency targets. This paper employed the method of normative legal and sociological approaches. Results show that the South Labuhanbatu Regency Government is working to achieve rice self-sufficiency through various policies and programs. Support from various parties, including the Indonesian National Armed Forces, the Indonesian National Police, and private companies, has also been instrumental in achieving this target. These efforts include increasing the cropping index, optimizing land use, and utilizing agricultural technology. The South Labuhan Batu Regency government has also implemented several policies aimed at food security to increase rice self-sufficiency in the regency. Food policies in South Labuhan Batu Regency are in accordance with the legal principles of food security. However, currently, there is no explicit food policy that leads to rice self-sufficiency in South Labuhan Batu Regency.